2022
DOI: 10.1111/jcpp.13714
|View full text |Cite
|
Sign up to set email alerts
|

Testing different sources of environmental unpredictability on adolescent functioning: ancestral cue versus statistical learning and the role of temperament

Abstract: Background The dimensional model of environmental adversity highlighted the effects of an unpredictable environment in promoting risky development. Toward gaining greater specificity in understanding, this multimethod, longitudinal study investigated the role of two sources of environmental unpredictability—ancestral cues versus statistical learning, and their interaction with dove temperament conceptualized within the evolutionary model of temperament, in shaping adolescent functioning. Methods Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Another exciting and growing area of research focuses on associations of childhood unpredictability with physiological processes and brain development. Though this area of research is relatively sparse in humans, we will highlight four papers from this growing area with outcomes that include vagal reactivity (Li et al, 2023), cortisol regulation (Doom et al, 2018), development of the uncinate fasciculus (Granger et al, 2021), and salience network integrity (Jirsaraie et al, 2023). Li et al (2023) tested whether unpredictability and adolescent temperament interacted to predict vagal (parasympathetic) reactivity in response to a family conflict discussion task.…”
Section: Physiology and Brain Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Another exciting and growing area of research focuses on associations of childhood unpredictability with physiological processes and brain development. Though this area of research is relatively sparse in humans, we will highlight four papers from this growing area with outcomes that include vagal reactivity (Li et al, 2023), cortisol regulation (Doom et al, 2018), development of the uncinate fasciculus (Granger et al, 2021), and salience network integrity (Jirsaraie et al, 2023). Li et al (2023) tested whether unpredictability and adolescent temperament interacted to predict vagal (parasympathetic) reactivity in response to a family conflict discussion task.…”
Section: Physiology and Brain Developmentmentioning
confidence: 99%
“…Though this area of research is relatively sparse in humans, we will highlight four papers from this growing area with outcomes that include vagal reactivity (Li et al, 2023), cortisol regulation (Doom et al, 2018), development of the uncinate fasciculus (Granger et al, 2021), and salience network integrity (Jirsaraie et al, 2023). Li et al (2023) tested whether unpredictability and adolescent temperament interacted to predict vagal (parasympathetic) reactivity in response to a family conflict discussion task. This study found that adolescents with low dove temperament (low inhibition, high boldness and exploration) showed blunted vagal reactivity under high levels of family instability compared to adolescents with high dove (high inhibition, low exploration) temperaments.…”
Section: Physiology and Brain Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The 'ancestral cues' and 'statistical learning' hypotheses are mutually compatible: people may combine ancestral and learned cues in developing models of their world [103] (Figure I). Empirical work suggests that people may vary in the extent to which they rely on each type of cue [108].…”
Section: Box 3 How Do People Assess Environmental Conditions To Guide...mentioning
confidence: 99%
“…It is consistent with multiple statistical formalizations of change over time. For example, one researcher might compute variance in harshness across the measurement period (e.g., Li et al, 2018Li et al, , 2022. Another might track abrupt shifts in the mean or variance in harshness (i.e., changepoints; described in Young et al, 2020).…”
Section: Introductionmentioning
confidence: 99%